Unemployment Reduction Targets to Realise NationalL Development Plan Vision 2030 - Blom, Phenyo; Jahed, Mohammed; Vyas-Doorgapersad, Shikha (Journal of Economic Development, Environment and People, 2023)
One of the main and most dynamic challenges confronting South Africa is the high unemployment rate, which has been increasing more rapidly than the country’s economic growth. The unemployment rate is increasing every year, supplemented with financial crisis as the South African economy is experiencing a drastic recession and jobs are getting lost. In 2012, the National Planning Commission (NPC) implemented a new long-term strategy, the National Development Plan Vision 2030 (NDP), which is set over an 18-year period (2012 to 2030). The NDP was introduced to meet the government’s objectives, which include economic growth, reducing triple challenges (unemployment, poverty and inequality) and improving service delivery. The main aim of the research is thus to assess the progress of the unemployment reduction targets set by the NDP, as well as recommend strategies that can be implemented to attain the unemployment reduction target and reduce unemployment to (under) 6%. The study employed a qualitative research method and a case study research design. Through literature review, information was compiled through studying budget reviews, the Public Finance Management Act (PFMA), press releases from international capital markets (International Monetary Fund and World Bank), official government documents, academic/scholarly newspapers, and relevant legislation. The finding explore that many factors hinder or impede the government from achieving its objectives, such as slow economic growth, the impact of Covid-19 on the labour market, skills gap and mismatch, the education system in South Africa and a severe lack of entrepreneurship. The article makes policy recommendations for improvement.